Integrated Education System: a Local Wisdom-Based Education Model for Building Student’s Character - Hasnadi, Hasnadi (International Journal of Educational Research & Social Sciences, 2023)
The advancement of information and technology impacts education and students’ character. An integrated education system is a solution that the government and people of Aceh district believe can build students’ character. This article aims to describe the integrated education system as an educational model based on local wisdom in building students’ character. This research is a qualitative research. Data were collected through observation, interviews and document study. Meanwhile, data analysis was carried out qualitatively. The results of the study concluded that: Integrated education is carried out in the morning and evening. The program includes both diniyah and tahfidz lessons. Malay-Arabic books that are taught at the study hall and dayah in Aceh Besar District are used as learning resources that are relevant to teaching materials. The learning methods applied are qudwah, 'aadah, mau'idzah, muraqabah, and uqubah. Characters was build through activities at school so that it becomes a habit